From Bluetooth naming to crowd interaction - José, Rui (2009)
In this paper, we describe how Bluetooth presence and naming can be used as the basis for crowd interaction. We also propose a number of exercises for the workshop where we hope to explore in-loco the emergence of multiple types of crowd behaviour.